(untitled) (Indian Journal of Arid Horticulture, 2025)
The study on impact assessment of integrated nutrient management practices in cumin revealed that application of NPK @ 50:30:20 kg/ ha with FYM @ 15 t/ ha FYM (T11) performed better at 45 DAS, 90 DAS and at harvest respectively, in terms of plant height, number of branches per plant, and plant population. Treatment T11 was also shown to have the best results for test weight, seed yield, quantity of umbels and seeds per plant. This demonstrate the effectiveness of INM in increasing cumin production and growth, providing important information for growing cumin in western Rajasthan.